2008
DOI: 10.1111/j.1467-9477.2008.00203.x
|View full text |Cite
|
Sign up to set email alerts
|

Retrospective Voting and Electoral Volatility: A Nordic Perspective

Abstract: This article examines why people vote for the same party, switch parties or move from voting to non‐voting at consecutive elections. By using post‐election survey data from Iceland, Finland, Norway and Sweden in the beginning of the 2000s, the main aim is to model the impact of retrospective evaluations of party performance while controlling for theoretically relevant variables. The results of the multinomial regression analyses confirm that dissatisfaction with the performance of a party correlates strongly w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
52
1
3

Year Published

2013
2013
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 50 publications
(56 citation statements)
references
References 58 publications
0
52
1
3
Order By: Relevance
“…According to Soderlund, this finding seems to indicate that shifts in voting behaviour should be interpreted as the products of rational judgments about past performances instead of being seen as symptoms of political frustration. This also means that disappointment about a particular party does not necessarily translate into general dissatisfaction with the political system, which contradicts Zelle's frustrated floating voter hypothesis (Soderlund, 2008). In their analysis of the determinants of party switching in 36 elections held in 22 advanced democracies, Dassonneville, Blais and Dejaeghere (2015) came to the same conclusion as that drawn by Soderlund.…”
Section: Theoretical Frameworkmentioning
confidence: 48%
See 4 more Smart Citations
“…According to Soderlund, this finding seems to indicate that shifts in voting behaviour should be interpreted as the products of rational judgments about past performances instead of being seen as symptoms of political frustration. This also means that disappointment about a particular party does not necessarily translate into general dissatisfaction with the political system, which contradicts Zelle's frustrated floating voter hypothesis (Soderlund, 2008). In their analysis of the determinants of party switching in 36 elections held in 22 advanced democracies, Dassonneville, Blais and Dejaeghere (2015) came to the same conclusion as that drawn by Soderlund.…”
Section: Theoretical Frameworkmentioning
confidence: 48%
“…He demonstrated that the probability of vote switching was strongly influenced by retrospective evaluations of performances of the party the respondent had voted for in the previous elections. Citizens tended to remain loyal to the party they had previously voted for if they thought that it had done a good job during the inter-election period, and conversely, voters were inclined to change parties if they considered that their previously endorsed party had performed poorly (Soderlund, 2008). Remarkably, the relationship between perceived party performances and vote switching remained robust even after controlling for the variables associated with general dissatisfaction with politics.…”
Section: Theoretical Frameworkmentioning
confidence: 67%
See 3 more Smart Citations